Hubungan Penguasaan Kosakata Dengan Kemampuan Menulis Karangan Narasi Pada Siswa Kelas IV SD Negeri 106812 Bandar Klippa - Indah Purnama Sari Siregar; Leni Malinda; Emy Hariati (CV. ITTC INDONESIA, 2024)
This research aims to: 1) describe the vocabulary mastery of class IV students at SD Negeri 106812 Bandar Klippa; 2) describe the ability to write narrative essays in fourth grade students at SD Negeri 106812 Bandar Klippa; and 3) examine the relationship between vocabulary mastery and the ability to write narrative essays in class IV students at SD Negeri 106812 Bandar Klippa. This type of research is correlation research. The sample for this research was 56 grade IV students at SD Negeri 106812 Bandar Klippa. The sample in this study used a proportional random sampling technique. Data collection techniques use tests and documentation. Data analysis uses product moment correlation. Based on the research results, it is known that: 1) students' overall vocabulary mastery obtained an average score of 62.2 in the quite good category; 2) students' overall ability to write narrative essays obtained an average score of 64.2 in the quite good category; and 3) there is a relationship between vocabulary mastery and the ability to write narrative essays in fourth grade students at SD Negeri 106812 Bandar Klippa of 0.920 with a very strong correlation category (rcount= 0.920 at the real level α= 0.05 with N= 56, rtable= 0.259 , and rh>rt). Based on the research data, it can be concluded that there is a positive relationship between vocabulary mastery and the ability to write narrative essays in class IV students at SD Negeri 106812 Bandar Klippa. This shows that the vocabulary mastery variable can be a good predictor of the ability to write narrative essays. So this research indicates that teachers who teach Indonesian language lessons must be able to improve vocabulary mastery to improve the ability to write narrative essays.